Successful Surgical Repair of Upper Eyelid Lacerations: A Case Series in Five Buffaloes - M Goriya, Yarmiben; Sangwan, Vandana; Gupta, Nikita; Kumar, Ashwani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study compiles five clinical cases of buffaloes presented with upper eyelid lacerations (laterally located) resulting from  trauma. The aim was to assess their clinical presentation, surgical repair, and healing outcomes. The duration between trauma and  presentation ranged from 1 to 25 days, with the causes mostly attributed to trauma from other buffalo, iron rod or unknown sources.  In one buffalo, the laceration was accompanied with prolapse of the lacrimal gland. The lacerations were surgically repaired under  sedation and auriculo-palpebral nerve block. Muscles and subcutaneous tissue were sutured in all cases (as per the availability), using  absorbable polyglactin 910 and the skin with non-absorbable nylon. The prolapsed lacrimal gland was successfully repositioned prior  to closure. The postoperative care included systemic antibiotics, anti-inflammatory medications and topical antibiotic eye ointments.  Out of 5 buffaloes, 4 could be followed and all buffaloes had uneventful healing. The study highlights the occurrence of upper lateral  eyelid lacerations with or without lacrimal gland prolapse in buffaloes and effectiveness of surgical intervention in restoring eyelid  integrity and ocular function, even if presented late.
Keywords: Buffalo; Eyelid; Laceration; Lacrimal gland prolapse; Surgery